Postoperative Changes in Strabismus, Ductions, Exophthalmometry, and Eyelid Retraction After Orbital Decompression for Thyroid Orbitopathy. Issue 4 (July 2017) - Rootman, Daniel B.; Golan, Shani; Pavlovich, Peter; Rootman, Jack
Abstract : Introduction: Surgical rehabilitation of thyroid orbitopathy involves reducing proptosis, treating strabismus, lengthening the eyelids, and managing aesthetic changes. Not all are necessary in each patient; however, they often are. The current investigation intends to describe postdecompression changes that may influence the staging of these procedures. Methods: In this retrospective cohort study, records of 169 patients who underwent orbital decompression between 1983 and 2001 were reviewed. A single orbital specialist confirmed all measurements. Time to follow up was defined as the most recent follow up after decompression and prior to any secondary procedures. No strabismus or eyelid surgery was performed at the time of decompression. Strabismus was measured with alternating prism cover test. Ductions were estimated utilizing Hirschberg's method. Exophthalmometry was measured with Hertel. Eyelid positions were defined relative to the pupillary light reflex. Strabismus data were analyzed within eye pairs. Ductions, exophthalmometry and eyelid position were analyzed for each eye. T -test for paired data was utilized to compare means pre- and postoperatively. Results: The study population was on average 45 years old and 73.4% women. Average length of follow up was 1.2 years. Esotropia was significantly increased after decompression by an average of 8.1 prism diopters ( p < 0.01). Exotropia and vertical deviations were not significantly altered. Ductions decreased by >5 degrees in at least one meridian for 68.1% of the population. Upper eyelid retraction remained unchanged; however, lower eyelid retraction improved by 50% from 1.4 mm to 0.7 mm ( p < 0.01). Exophthalmometry improved from 23.5 mm to 19.7 mm ( p < 0.01), and this result was correlated with the number of walls removed (Pearson r = −0.302, p < 0.01). Conclusions: On average, esotropia and ductions tend to worsen with decompression surgery. This result supports the clinical dictum to avoid strabismus surgery until after decompression. The improvement in lower eyelid retraction suggests that at least lower eyelid-lengthening surgery should be reserved for after decompression, as there may be significant spontaneous improvement, while the same may not be true for upper eyelid retraction, which does not tend to change with decompression. Abstract : In this cohort of 169 patients undergoing orbital decompression followed for a mean of 1.3 years, it was noted that on average, esotropia, ductions and lower eyelid position tend to change with decompression surgery while upper eyelid position did not. This result supports the clinical dictum to stage surgical rehabilitation in thyroid eye disease.